What should we call the 'crista'? - Anderson, R H (1977)
Review of published work concerning congenital cardiac anomalies reveals that at least four different structures have been described as the crista supraventricular, in addition to the structure which in the normally formed right ventricle separates pulmonary and tricuspid valves. Possibility of further confusion arises since at least two different structures have been described under the name 'septal band'. We suggest that this potentially confusing situation will be best resolved by reserving the term 'crista' for description of the muscle mass between inflow and outflow portions of the right ventricle when there are no additional outflow tract anomalies. We then suggest that at least three separate structures warrant description in hearts with outflow tract anomalies. The first separates the semilunar valves, the second separates a semilunar valve from an atrioventricular valve, and the third is an extensive septal trabeculation of the right ventricle. Our suggested terms for these structures are the infundibular septum, ventriculo-infundibular fold, and trabecula septomarginalis, respectively. However, we believe that such terms would be better decided and agreed upon within an internationally formulated 'Nomina Cardiologica', a terminology as yet lacking in congenital heart disease.